EFFECTS OF ORGANIC AND CHEMICAL FERTILIZER INPUTS ON BIOMASS PRODUCTION AND CARBON DYNAMICS IN A MAIZE FARMING ON ULTISOLS - Maswar Maswar; Yoyo Soelaeman (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2016)
An effort to increase the yield and reduce carbon loss from maize farming practices on Ultisols largely depend on fertilizer inputs and in situ crop residual management. The experiment aimed to estimate yields, biomass production and carbon dynamics of several management fertilization on maize farming practice on Ultisols has been conducted from March to July 2013 in Taman-bogo Experimental Farm, East Lampung. The experiment was set up as a randomized complete blockdesign, consisted of 6 treatments namely: 5 t ha-1 of cattle manure, 5 t ha-1of dried sludge manure, and its combination with 200 kg urea ha-1 + 125 kg SP36 ha-1 + 50 kg KCl ha-1 (50% of recommended dose of inorganic fertilizers “RDIF”) and 75% of RDIF. The experimental results revealed that application of combined organic with inorganic fertilizers increased the biomass production, carbon fixation, and grain yield significantly. More than 50% of produced biomass and fixed carbon (grain, maize cob, maize husk, stems and leaves) were removed from maize farming. The use of organic fertilizer combined with NPK fertilizer at 50% of RDIF can be applied to increase the biomass production, organic carbon fixation and maize grain yield in sustainable ways.